Power Supply Ensuring Measures and Implications of Foreign Countries' Power Systems with High Proportion of New Energy - Xiaoning YE; Caixia WANG; Qionghui LI; Chao YANG (Zhongguo dianli)
With the global energy transformation and the rapid development of new energy, the power supply security issue of the power system with high proportion of new energy has become increasingly prominent and attracted focal attentions in some countries. Firstly, we analyzed in detail the power output characteristics of new energy and its challenges to power supply security in power balance and load support degree. Secondly, by selecting Germany, the United States, Japan and other typical countries with a relatively high proportion of new energy development, we made an in-depth study of their practical experience of ensuring the safe and reliable power supply in the power system with a high proportion of new energy from three aspects of policies and regulations, monitoring and early warning, dispatching and operation management. Finally, based on the actual situation of China's new power system construction, we proposed the implications for China's new energy development, which can provide a certain reference for China's power supply security.